Communication Typology of Betawi People in The Virtual Community - Zikrulloh, Zikrulloh (SOURCE : Jurnal Ilmu Komunikasi, 2024)
Inter-ethnic mixing in Jakarta means the existence of Betawi culture is no longer intact and eliminates the distinctive values of Betawi culture, causing the Betawi people to adapt by using internet technology to interact. This study aims to explain how the Betawi people use virtual communities to represent their original culture to other heterogeneous cultures. This study uses a qualitative method with a netnography approach based on the typology of communication initiated by Alan Rubin (1981). The study population is every form of communication, whether text, images, or videos, uploaded by each community member to the Persatuan Betawi Facebook group. The study results portray that Betawi people utilize the virtual Facebook community through a communication typology consisting of passing time, companionship, escape, enjoyment, social interaction, relaxation, information, and excitement. The study results also show that the presence of virtual communities also influences the social empathy of community members in the real world.